APPROXIMATION OF SOLUTIONS OF SPLIT INVERSE PROBLEM FOR MULTI-VALUED DEMI-CONTRACTIVE MAPPINGS IN HILBERT SPACES
Let H_1 and H_2 be real Hilbert spaces and A_j : H_1 to H_2, (1 leq j leq r) be bounded linear linear operators, U_i : H_1 to 2^H_1 , (1 leq i leq n) and T_j : H_2 to 2^H_2 , (1 leq j leq r) be multi-valued demi-contractive operators. An iterative scheme is constructed and shown to converge weakly to a solution of generalized split common fixed points problem (GSCFPP). Under additional mild condition, the scheme is shown to converge strongly to a solution of GSCFPP. Moreover, our scheme is of special interest. , number=1, journal=Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), author=Bello, A.U. and Chidume, C.E. and Isyaku, M., year=2020, month=Jan., pages=15–28